Building Personality from Al-Ghazalī’s Perspective: Critical Study of Freud's Psychoanalytic Theory - Jarman Arroisi; Diana Aristika Putri; Muhammad Fahmi Amrullah (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
The issue of human behaviours is still engaging to discuss as human behaviour constantly changes. This study aims to reveal the problem of the psychoanalytic theory of Sigmund Freud, which has been the primary reference in the discussion of modern psychology. Modern psychologists tend to neglect the role of religion due to secularization in various aspects of life. This paper is library-based research that employs a comparative-analysis method. This study reveals that personality studies in modern psychology disregard the role of God. Humans deny God's power outside themselves, leading to modern man's spiritual crisis. In addition, the psychoanalytic theory does not deal with the spiritual aspect, so this theory is no longer relevant as a solution to modern human personality problems. Third, the concept of tazkiyat an-nafs and insān kāmil in the Islamic tradition can guide human life amid a spiritual crisis and guide humans to return to their God. Contribution: This article reveals that the most effective solution in dealing with modern humans' personality and spiritual crises is to return to the initial nature of humans as creatures of God who are always obedient to Him.